Short‐term response of fish communities and water chemistry to breaching of a causeway in the Sarita River Estuary, British Columbia, Canada. Issue 6 (19th August 2019) - Gerwing, Travis G.; Plate, Elmar; Sinclair, Jesse; Burns, Christopher; McCulloch, Cameron; Bocking, Robert C.
Abstract : On the west coast of Vancouver Island, Canada, in the Treaty Settlement Lands of the Huu‐ay‐aht First Nation, a causeway isolating the southern portion of the Sarita River estuary was breached in 2018 to enhance juvenile salmon and tidal water access into the southern portion of the estuary. Short‐term goals of breaching were to: (1) enhance juvenile salmon access through the causeway; (2) promote colonization of Chinook and Chum Salmon in pools, while retaining Coho Salmon; (3) monitor the entire estuary fish community, including non‐salmonids, to assess breaching success; and (4) homogenize water chemistry in pool and channel ecosystems currently fragmented by the causeway. Immediately following the breach, both fish community and water chemistry measurements indicate that these goals were achieved. Chinook and Chum Salmon utilization increased inside and outside of the causeway following breaching. Similarly, Chinook and Chum salmon were observed in pool ecosystems, and Coho Salmon were also retained in pools following breaching. Water chemistry was homogenized post‐breach, primarily due to increased saltwater penetration. While continued monitoring is required, short‐term indicators suggest that breaching was effective in increasing connectivity of the Sarita Estuary, allowing access to 1.4 km 2 of habitat that had previously been inaccessible to juvenile salmon.